Anaesthesia in PROstate Biopsy Pain Obstruction Study: A Study Protocol for a Multicentre Randomised Controlled Study Evaluating the Efficacy of Perineal Nerve Block in Controlling Pain in Patients Undergoing Transperineal Prostate Biopsy - He, Bi-Ming; Li, Rong-Bing; Wang, Hai-Feng (Frontiers in Surgery, 2021)
Introduction Transperineal prostate biopsy is as effective as the transrectal biopsy in detecting prostate cancer and has a lower risk of infection. However, concerning the procedural pain of the transperineal route, a higher level of anaesthesia is needed, which prevents this approach from being widely used. Although several methods of local anaesthesia to relieve pain during transperineal biopsy have been described, few well-designed trials have been conducted to assess the efficacy of local anaesthesia. Methods This is a prospective, multicentre, randomized controlled study in men suspected of having prostate cancer and planning to undergo transperineal prostate biopsy. The aim of this trial is to determine whether the perineal nerve block and periprostatic block relieve pain to different extents in men undergoing transperineal biopsy. The main inclusion criteria are men aged between 18 and 80 years old, a prostate-specific antigen (PSA) level of 4 – 20ng/ml, or/and suspicious rectal examination findings. A sample size of 190 participants, accounting for a 10% loss, is required. All participants will be randomly allocated at a ratio of 1:1 to the perineal nerve block (n=95) and periprostatic block groups (n=95). The primary outcome will be the level of the worst pain experienced during the transperineal prostate biopsy procedure, which will be measured by a numerical rating scale (NRS). The key secondary outcomes will include the pain severity score at 1, 6, and 24 hours after prostate biopsy. Conclusion Anaesthesia in PROstate biopsy Pain Obstruction Study (APROPOS) is randomized controlled trial aiming to determine the efficacy of the perineal nerve block in controlling pain in patients undergoing prostate biopsy via the transperineal approach.